The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2023
DOI: 10.3390/bioengineering10020179
|View full text |Cite
|
Sign up to set email alerts
|

Knee Joint Contact Forces during High-Risk Dynamic Tasks: 90° Change of Direction and Deceleration Movements

Abstract: Pivoting sports expose athletes to a high risk of knee injuries, mainly due to mechanical overloading of the joint which shatters overall tissue integrity. The present study explored the magnitude of tibiofemoral contact forces (TFCF) in high-risk dynamic tasks. A novel musculoskeletal model with modifiable frontal plane knee alignment was developed to estimate the total, medial, and lateral TFCF developed during vigorous activities. Thirty-one competitive soccer players performing deceleration and 90° sideste… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
2
1

Year Published

2023
2023
2024
2024

Publication Types

Select...
3
2

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 59 publications
(87 reference statements)
1
2
1
Order By: Relevance
“…in the start position) to 4 kN at the maximal squat depth. These values correspond to the range of 0.58 to 4.6 body weights (BW) and, generally are close to data, reported in the literature for squatting [10] and high-risk dynamic tasks [38], and are reasonably higher, than forces, reported for walking/running [15]. The force maximums generally coincided with the sensor readouts, and hence, with plantar pressure maximums.…”
Section: Correlation Between Knee Joint Force and Sock Sensor Datasupporting
confidence: 87%
“…in the start position) to 4 kN at the maximal squat depth. These values correspond to the range of 0.58 to 4.6 body weights (BW) and, generally are close to data, reported in the literature for squatting [10] and high-risk dynamic tasks [38], and are reasonably higher, than forces, reported for walking/running [15]. The force maximums generally coincided with the sensor readouts, and hence, with plantar pressure maximums.…”
Section: Correlation Between Knee Joint Force and Sock Sensor Datasupporting
confidence: 87%
“…The range of joint contact forces of the hip, knee, and ankle joints predicted by the current study is comparable to previous studies. 12,16,17,22,[35][36][37] Prior simulation studies reported hip joint forces during slow to fast runs to be 7.5-10.0 BW 16 with speed range (0.8 to 3.6 m/sec), compared to our predicted 8.2-11.6 BW. Knee joint forces were reported around 7.8-12.0 BW at 4.36 m/sec 12,22 , while our prediction was 9.7-10.5 BW.…”
Section: Discussioncontrasting
confidence: 53%
“…50,51 Single studies evaluated the effects of sex, 52 speed, 53 lab versus field, 54 limb differences, 55 cutting on a softball base compared to a flat surface, 56 and the joint contact forces of the medial versus the lateral tibiofemoral joint (table 2). 57 The median number of participants was 24 .…”
Section: Cuttingmentioning
confidence: 99%